Assessment of biogrowth assemblages with depth in a seawater intake system of a coastal power station. Issue 5 (24th May 2021) - Subba Rao, T.; Murthy, P. S.; Veeramani, P.; Narayanan, D. S.; Ramesh, R.; Jyothi, B. N.; Muthukumaran, D.; Murugesan, M.; Vadivelan, A.; Dharani, G.; Santhanakumar, J.; Ramadass, G. A.
Abstract: Marine biogrowth infestation of a seawater intake system was investigated. A digital camera fixed onto a skid was used to record the biogrowth at intervals of 5 m up to a depth of 55 m. Divers inspected the intake shaft and collected the biogrowth samples for biomass estimation. A biomass density of 7.5 kg m −2 and 28.2 kg m −2 was recorded at 5 and 30 m depths respectively. Inspection by the divers revealed that hard-shelled organisms such as oysters and brown and green mussels were observed in plenty up to a thickness of 15 cm and bryozoans grew as epibionts. At lower depths (<40 m), hydroids grew on the shells of green mussels along with silt accumulation. The biofouling community was composed of 46 organisms, exhibiting variation in distribution and abundance. The study explains the extent and type of marine biogrowth phenomena with depth and describes biofouling preventive methods. Supplemental data for this article is available online at https://doi.org/10.1080/08927014.2021.1933457 .